Associations Between Sleep Quality and Migraine Frequency: A Cross-Sectional Case-Control Study. Issue 17 (April 2016) - Lin, Yu-Kai; Lin, Guan-Yu; Lee, Jiunn-Tay; Lee, Meei-Shyuan; Tsai, Chia-Kuang; Hsu, Yu-Wei; Lin, Yu-Zhen; Tsai, Yi-Chien; Yang, Fu-Chi
Abstract : Abstract: Migraine has been associated with sleep disturbances. Relationship between sleep quality and migraine frequency is yet to be determined. The present study aimed to investigate sleep disturbances among low-frequency, moderate-frequency, high-frequency, and chronic migraineurs, with and without auras, with well-controlled confounding variables. This cross-sectional controlled study included 357 subjects from an outpatient headache clinic in Taiwan. Standardized questionnaires were utilized to collect demographic, migraine, sleep, depression, anxiety, and restless leg syndrome characteristics in all participants. According to frequency of migraine attacks, patients were divided into 4 groups: with 1 to 4 migraine days per month, 5 to 8 migraine days in a month, 9 to 14 migraine days in a month, and >14 migraine days per month. The Pittsburgh Sleep Quality Index (PSQI) and subgroup items were used to evaluate sleep quality. The association between migraine frequency and sleep quality was investigated using multivariable linear regression and logistic regression. The PSQI total score was highest in patients with high frequent migraine (10.0 ± 3.4) and lowest in controls (7.0 ± 3.4) with a significant trend analysis ( P for trend = 0.006). Migraine frequency had an independent effect on the items "Cannot get to sleep within 30 minutes" ( P < 0.001), "Wake up in the middle of the night or early morning" ( P < 0.001), "Bad dreams" ( P = 0.001), "Pain" ( P = 0.004), and "Quality of sleep" ( P < 0.001). The result showed the effect of migraine frequency in both the aura-present ( P for trend = 0.008) and the aura-absent subgroups ( P for trend = 0.011). High migraine frequency correlates with poor sleep quality and a higher prevalence of poor sleepers. These associations occur in migraine with aura and without aura.